T cell selection during the evolution of CD8+ T cell memory in vivo. - Callan, M; Annels, N; Steven, N; Tan, L; Wilson, J; Mcmichael, A; Rickinson, AB (1998)
Memory T cell responses are frequently highly restricted in terms of receptor usage. How and when such clonotypic dominance is established remains poorly understood. Here we have investigated the evolution of the T cell responses to an epitope from Epstein-Barr virus (EBV), (FLRGRAYGL), by analyzing TCR use of clones specific for this epitope, derived from peripheral blood mononuclear cells taken from individuals early during primary EBV infection and up to 3 years later. We show that, in a given individual, particular T cell clonotypes are selected early during the primary response to this epitope and that the same clonotypes dominate the late memory response. In one individual direct analysis of HLA-B8-restricted FLRGRAYGL-specific T cells, isolated from peripheral blood lymphocytes taken during primary EBV infection using a tetrameric MHC-peptide complex, confirmed the early selection of the dominant clonotypes.